The Chinese Yuan : internationalization and financial products in China - Zhang, Peter G.; Chan, Thomas (Wiley finance, 2011)
* Few topics have attracted as much attention worldwide in recent years as the RMB. * This book explores the ever-changing role of the RMB and the related derivative products